Estimating the Costs and Benefits of Local Government Reorganisation: A Case of Korea - Young-Chool Choi; Sang-Yeup Lee (European Regional Science Association (ERSA), 2006)
It appears that few empirical studies have been conducted which are aimed at estimating not only the costs but also the benefits surrounding local government reorganisation, either in academia or in government, and most reports on the issue seem to focus primarily on costs. In order to examine local issues such as reorganisation, however, in which many interested parties are controversially involved, both costs and benefits should be estimated objectively and disseminated in as many ways as possible before a referendum is conducted. This paper intends to bridge the gap between current levels of analysis and what is required for an accurate appraisal to be made of local government reorganisation. In it, we introduce the result of a research project conducted in relation to a local authority reorganisation plan implemented in Korea. The initiative seeks to create a unitary local authority replacing one first-tier and four second-tier local authorities within the first tier, in the hope of reducing the cost of providing services and also of making local authorities more competitive. This paper describes the research strategy employed to estimate the costs and benefits associated with local government reorganisation, and then we introduce the results of the analysis. The research process being described here gives us information about what should be included in the categories of costs and benefits, and what methodologies can be applied in estimating these. Finally the analysis shows how much the benefits and costs resulting from reorganisation will be.
Keywords: 330